Combination of red cell distribution width and procalcitonin as diagnostic biomarkers of neonatal sepsis in preterm infants - Irene Ratridewi; Savitri Laksmi Winaputri; Eko Sulistijono; Brigitta I. R. V. Corebima; Achmad Yunus (Indonesian Pediatric Society, 2023)
Background Diagnosis of neonatal sepsis is still challenging. Several diagnostics test have been developed to help diagnose of neonatal sepsis, but sometimes it could not be done routinely in limited facilities. Procalcitonin (PCT) and red cell distribution width (RDW) have been reported to have correlations with the risk of developing sepsis. Objective To evaluate the diagnostic value of combined of PCT and RDW as markers for neonatal sepsis in preterm infants. Methods A cross sectional study was conducted in the neonatal ward, Syaiful Anwar hospital, Malang, East Java. The subjects were preterm infants with neonatal sepsis. Blood culture were taken as the gold standard and RDW and PCT levels were assessed as the comparison. All of the test were performed at the begining of the study. The incidence of sepsis was reported as the main outcome. The data obtained were processed and analyzed using the receiver operating characteristic (ROC) method to obtain the area under curve (AUC) value. Results Fifty-five preterm infants presenting neonatal sepsis were enrolled in this study. The combination of RDW and PCT showed AUC 0.814 (P=0.199) with sensitivity and specificity 78.9% and 80.6%, respectively in diagnosing neonatal sepsis compared to blood culture. Conclusion Combination of RDW and PCT as markers of sepsis in preterm infants have good sensitivity and specificity.